ELICITING RISK AND TIME PREFERENCES IN AGRICULTURE: MODERN EXPERIMENTAL APPROACHES - Tadjiyev, Abdusame Abduxamidovich (THE INNOVATION ECONOMY, 2026)
This article analyzes the main methods used in behavioral economics to determine individuals’ risk and time preferences. In particular, it examines the self-assessment method, experimental approaches based on lottery choice, and the intertemporal choice method. The study emphasizes that measuring risk and patience is important for explaining economic decisions, especially in agriculture, investment, savings, and consumer behavior. It is also noted that methods based on real incentives provide more reliable results compared to hypothetical questions.